A study on development of river with healthy and sustainable plant biodiversity - Ibrahim, Zati Izni; Hj. Baharuddin, Zainul Mukrim (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
River has been a precious water source in our daily life for every living thing on earth including human being, animals, plants, and aquatic organisms. Nowadays, more rivers have been seriously polluted due to rise urbanization process and development of industry and infrastructure. Thus, people have responsibility to maintain the river, so that, it can be passed to the future generations. Generally, the main problem of the IIUM river is pollution that comes from the domestic waste that channelled straight to the river without any filtration. In addition, the abundance of silt and muddy water that comes from construction activity outside IIUM also pollutes the river. This research is discussing about the problems involving river by using the aquatic plants as the solution. In order to tackle this issues, the data was obtained by using the qualitative technique which involving literature reviews and observation. The research shows that the enhancement of IIUM river has the potential to become the university’s main attraction. Hence, the idea of uplifting this river into this university’s landmark can become reality, which will encourage more interaction between human and wildlife. A good design is a design where it is beneficial to human and simultaneously preserves the nature. Healthy living environment is a treasure to the coming generations because they deserve for healthy environment.